2022
DOI: 10.1007/s10006-022-01041-6
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of maxillofacial trauma during the 2020 COVID-19 lockdowns in Melbourne, Australia

Abstract: Purpose To compare the incidence, aetiology, and patterns of maxillofacial fracture presentations during the various stages of the 2020 Melbourne COVID-19 lockdown restrictions to periods outside lockdown in 2019 and 2020. Methods This is a retrospective study of 344 subjects. The patterns of facial trauma presentations to a tertiary hospital in metropolitan Melbourne during the 2020 COVID-19 restrictions were compared to periods with no restrictions over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 14 publications
4
18
0
1
Order By: Relevance
“…The statistical analysis conducted by the authors shows a much lower percentage of domestic trauma in 2019 than in 2020; these were mainly due to accidental falls of elderly patients (76.67% in 2019 vs. 25% in 2020). This is also reported in other studies that attest a decrease in the rate of road accidents and sports-related injuries (4.17% in 2020 vs. 20% in 2019) due to the confinement and isolation measures adopted by governments [ 1 , 17 , 18 , 19 , 20 ]. The most important issue is the increase in domestic trauma from interpersonal violence, especially against women and children, recorded in 2020 compared to the previous year.…”
Section: Discussionsupporting
confidence: 85%
“…The statistical analysis conducted by the authors shows a much lower percentage of domestic trauma in 2019 than in 2020; these were mainly due to accidental falls of elderly patients (76.67% in 2019 vs. 25% in 2020). This is also reported in other studies that attest a decrease in the rate of road accidents and sports-related injuries (4.17% in 2020 vs. 20% in 2019) due to the confinement and isolation measures adopted by governments [ 1 , 17 , 18 , 19 , 20 ]. The most important issue is the increase in domestic trauma from interpersonal violence, especially against women and children, recorded in 2020 compared to the previous year.…”
Section: Discussionsupporting
confidence: 85%
“…This is the first epidemiologic study of maxillofacial fractures in Umbria, Italy, and one of few studies analyzing the impact of the COVID-19 pandemic on the epidemiology of maxillofacial traumas 16,18–24. Umbria has 870,165 inhabitants,25 an area of 8.456 km 2 and borders Lazio, Tuscany and Marche.…”
mentioning
confidence: 99%
“…16,17 This is the first epidemiologic study of maxillofacial fractures in Umbria, Italy, and one of few studies analyzing the impact of the COVID-19 pandemic on the epidemiology of maxillofacial traumas. 16,[18][19][20][21][22][23][24] Umbria has 870,165 inhabitants, 25 an area of 8.456 km 2 and borders Lazio, Tuscany and Marche. It is well known for its picturesque medieval villages (like Gubbio and Assisi, the town of Saint Francesco) that attract tourism, mainly for religious purposes.…”
mentioning
confidence: 99%
“…False negatives due to SARS-CoV-2 mutations, or poor collection, transport, or handling are also possible [ 11 ]. After reviewing the literature, we found that many other studies monotonously focused on facial trauma epidemiology during the pandemic [ 20 , 21 , 22 , 23 , 24 ]. To the best of our knowledge, this is the first case–control study concerning SARS-CoV-2-OSC in asymptomatic COVID-19 patients with OWF-PNS.…”
Section: Discussionmentioning
confidence: 99%